New Studies in Dogmatics : JUSTIFICATION - Horton, Michael (Zondervan, 2018)
The doctrine of justification stands at the center of our systematic reflection on the meaning of salvation as well as our piety, mission, and life together. In his two-volume work on the doctrine of justification, Michael Horton seeks not simply to repeat noble doctrinal formulas and traditional proof texts, but to encounter the remarkable biblical justification texts in conversation with the provocative proposals that, despite a wide range of differences, have reignited the contemporary debates around justification.